Impact of Orthodontic Decompensation on Bone Insertion. (10th November 2014) - Guedes, Fabio Pinto; Capelozza Filho, Leopoldino; Garib, Daniela Gamba; Nary Filho, Hugo; Borgo, Evandro José; Cardoso, Mauricio de Almeida
Abstract : There has always been concern in determining the relationship between orthodontic tooth movement and the consequent biological costs to the periodontium and tooth root. The possibility of evaluating the tooth and bone morphology by CBCT allows more accurate analysis of qualitative and quantitative aspects of these processes. This paper presents a case report of a 20-year-old male patient with Class III malocclusion and hyperdivergent facial pattern, who was surgically treated. A significant amount of labial movement of mandibular incisors was performed during orthodontic treatment before surgery. CBCT was used for evaluation of buccal and lingual bone plates before and after tooth decompensation. The changes in the bone insertion level of maxillary and mandibular incisors in the present case encourage a reflection on the treatment protocol in individuals with dentoskeletal discrepancies.